School leaving mathematical examination in Lithuania between the two world wars - Ragalytė , Birutė; Paukštienė, Alma (Lietuvos matematikos rinkinys, 2004)
The school leaving mathematical examination in Lithuania between the two world wars is discussed in this article. Types of problems at the school-leaving mathematical examination at this period are described. Problem solving task in 1929–1932 are presented. The results of investigation on how the college students were solving these problems are given here.
Keywords: mathematical examination in Lithuania between the two world wars; problems; research; analysis